PENGUKURAN PREFERENSI KONSUMEN BAKSO - Marta Catur Pamungkas; Banun Diyah Probowati; Iffan Maflahah (AGROINTEK, 2014)
Consumers make purchases based on certain choices. These options include product attributes and attribute level. Meatball has attributes such as texture, price, and taste. These attributes affect the consumer buying process . The aim  of this study was to determine the utility values for all attributes and attribute level of meatballs that have been selected by consumers. This research is  a qualitative and quantitative research conducted in Bangkalan Regency. Respondents of this study consisted of 60 people. The results of this research  revealed that the value of the utility for the level of preference of texture was soft texture with a utility value of  0.058, meatballs price at Rp 500.00 with utility value of 0.006, and the selected flavor attributes are taste spicy sauce with  utility value of 0.36. Attributes to contribute to consumer's decision to buy meatballs were flavor at 63.321 % , texture at 20.114 % and meatball price at 16.565 % contribution